2014
DOI: 10.1001/jamafacial.2013.2348
|View full text |Cite
|
Sign up to set email alerts
|

The Tripod Graft

Abstract: IMPORTANCE Nasal tip revision remains one of the most challenging surgical procedures for facial plastic surgeons to perform.OBJECTIVE To describe preoperative and postoperative findings related to nasal tip functional and aesthetic aspects following revision rhinoplasty using the "tripod" technique. DESIGN, SETTING, AND PARTICIPANTSA retrospective descriptive study was performed in patients who underwent revision rhinoplasty between 2007 and 2012 at a clinic in Bogota, Colombia. A preoperative diagnosis of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Zeng et al 45 reported a “mushroom” combination graft composed of columellar strut with cap graft. Pedroza et al 46 addressed lateral cartilages as well as columellar retraction by utilizing a combination of seagull wing and shield grafts. Bracaglia et al 47 introduced a “rainbow graft,” which resolves asymmetry, dome angulation with cartilage interruption, alar pinch and retraction, and underprojection, all with a single graft.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al 45 reported a “mushroom” combination graft composed of columellar strut with cap graft. Pedroza et al 46 addressed lateral cartilages as well as columellar retraction by utilizing a combination of seagull wing and shield grafts. Bracaglia et al 47 introduced a “rainbow graft,” which resolves asymmetry, dome angulation with cartilage interruption, alar pinch and retraction, and underprojection, all with a single graft.…”
Section: Discussionmentioning
confidence: 99%
“…The alar spreader graft has historically been used to correct pinched tip deformity but is another option when attempting to correct medialization of the lateral crus, a potential cause of alar retraction. Kim et al suggest using alar spreader when simultaneously correcting alar retraction and an upturned tip [35,53] . In this scenario, both deformities can be addressed with the release of the nasal hinge and the scroll area, which helps to correct the upturned tip abnormality and simultaneously is a necessary step prior to alar spreader graft placement.…”
Section: Correctionmentioning
confidence: 99%